Mapping the Number of Patients Undergoing Treatment and Care in Public Hospitals After the Covid-19 Pandemic - Lenni Dianna Putri; Ermi Girsang; I Nyoman Ehrich Lister; Evizal Abdul Kadir (Universitas Islam Indragiri, 2026)
The COVID-19 pandemic has had profound impacts on healthcare systems globally, altering the patterns of patient care and treatment in public hospitals. This research aims to map the number of patients undergoing treatment and care in public hospitals following the pandemic, providing insights into the evolving healthcare landscape. Utilizing data from public hospitals, we analyzed trends in patient admissions, treatment types, and care requirements post-pandemic. Our findings reveal a significant shift in healthcare demands, with an increase in patients requiring long-term care and treatment for chronic conditions exacerbated by delayed medical attention during the pandemic. Additionally, mental health services have seen a notable surge in utilization, reflecting the psychological toll of the pandemic. The research highlights the need for adaptive healthcare strategies to address the changing patient demographics and ensure efficient resource allocation. These insights can guide policymakers and healthcare providers in optimizing patient care and improving healthcare delivery in the post-pandemic era.